The Future of Coaching: A Conceptual Framework for the Coaching Sector From Personal Craft to Scientific Process and the Implications for Practice and Research - Passmore, Jonathan; Evans-Krimme, Rosie (Frontiers in Psychology, 2021)
This conceptual paper explores the development of coaching, as an expression of applied positive psychology. It argues that coaching is a positive psychology dialogue which has probably existed since the emergence of sophisticated forms of language, but only in the past few 1000years, has evidence emerged of its use as a deliberate practice to enhance learning. In the past 50years, this dialectic tool has been professionalised, through the emergence of professional bodies, and the introduction of formal training and certification. In considering the development of the coaching industry, we have used Rostow’s model of sector development to reflect on future possible pathways and the changes in the coaching industry with the clothing sector, to understand possible futures. We have offered a five-stage model to conceptualise this pathway of development. Using this insight, we have further reviewed past research and predicted future pathways for coaching research, based on a new ten-phase model of coaching research.